The Strategic Tech Horizons: A Comprehensive SWOT Analysis of Organizational Technology Integration - Paroli, Paroli; Jajang Sugiat; Suca Rusdian (Takaza Innovatix Labs Ltd., 2023)
This article conducts a comprehensive SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis focused on the strategic integration of technology within Bank BJB, Garut. The strengths identified include the bank's established local presence, a robust customer base, and a strong financial position. However, the analysis reveals weaknesses, including limited experience in digital banking, reliance on traditional processes, and potential resistance to change. Opportunities lie in the growing demand for digital banking services, collaborative partnerships with fintech companies, and regulatory support for technological advancements. On the flip side, the bank faces threats such as intense competition from national and global banks, cybersecurity risks, and the risk of rapid technological obsolescence. The discussion emphasizes the need for strategic initiatives to capitalize on strengths, address weaknesses, seize opportunities, and mitigate threats. In conclusion, recommendations are provided, urging Bank BJB to invest in digital literacy, establish strategic fintech partnerships, fortify cybersecurity measures, and foster a culture of innovation to navigate the dynamic landscape of technology integration successfully.